Synthesis and duplex-forming ability of oligonucleotides modified with 4′-C, 5′-C-methylene-bridged nucleic acid (4′, 5′-BNA). (15th September 2021) - Yamaguchi, Takao; Yamamoto, Chika; Horiba, Masahiko; Aoyama, Hiroshi; Obika, Satoshi
Graphical abstract: Abstract: We describe herein the design and synthesis of 4′- C, 5′- C -methylene-bridged nucleic acid (4′, 5′-BNA), a novel artificial nucleic acid with the torsion angle γ in a non-canonical + ac range. The 4′, 5′-BNA phosphoramidite bearing a thymine nucleobase was synthesized from a commercially available thymidine analog in 11 steps and successfully incorporated into oligonucleotides. The resulting oligonucleotides were evaluated for their duplex-forming ability toward single-stranded DNA and RNA.